RANCANG BANGUN SISTEM MONITORING KUALITAS AIR BERBASIS IoT (INTERNET OF THINGS) PADA TAMBAK IKAN BANDENG - Maharani, Farah Ardhia; Fathurahman, Mohamad; Rachman, Adam (Spektral, 2024)
One of the main factors to consider in milkfish aquaculture in ponds is maintaining the environmental sustainability of the water. Therefore, the water quality in milkfish ponds must be monitored daily. To facilitate periodic water quality monitoring for milkfish farmers, a pond water quality monitoring system was developed for smartphones. This system monitors water salinity levels using a TDS sensor, pH levels using a pH sensor, water temperature using a DS18B20 sensor, and water turbidity using a turbidity sensor, all directly connected to a WEMOS D1 microcontroller. All parameters are monitored through a custom Android application, which sends notifications if any water parameter exceeds normal limits: temperature 15-40°C, salinity 5-35 ppt, pH 7-8, and turbidity 20-40 NTU. The microcontroller programming is done in C, and Python is used to process real-time data from the database into Ms. Excel files. System testing is carried out on each sensor to determine the level of accuracy using a comparative measuring instrument. The results show that the system communicates effectively, sending and receiving sensor data every 5 seconds, with an overall sensor reading accuracy of 99.1%.